Laughter's Fury: The Double Bind of Black Laughter - Millan, Diego. (2017)
Abstract: Laughter's Fury advances two major claims: that western philosophical and cultural traditions marginalize Blackness within theories of laughter, and that laughter's sonic disruptiveness contributes to the intellectual development of a Black radical consciousness. Reading theories of laughter alongside black literature of the nineteenth and twentieth centuries, this project bridges the two historically separate strands of scholarship - Black Studies and Humor Studies. The disproportionate way in which humor scholars fasten laughter to affects such as joy overinvests laughter with a sense of goodness; consequently, this idea of laughter as an act of affirmation occludes how laughter operates in modes of protest and rebellion. Most theories of comedy uphold an Aristotelian premise that laughter is "essentially human," which extends laughter's status as good to the safeguarding of Western definitions of the human. Yet as scholars such as Sylvia Wynter and Saidiya Hartman have illustrated, the emergence of Western civilization and liberal humanism depended on the violent, repeated repudiation of blackness and of Black subjectivity. I ground my project in the perspective granted by this foundation in critical theory and cultural analysis to examine laughter's role in securing the boundaries of the human and examine the double bind of black laughter within the US cultural imaginary - the impasse that appears when laughter is associated with life and positivity by a culture that equates Blackness with negativity and death. I examine the ways that laughter circulates within a Black cultural imaginary in relation to a diverse and interdisciplinary range of sources: literary, historical, and theoretical. Calling upon these varied sources, each chapter traces a different avenue for considering laughter's role in Black literature: undoing western epistemology (chapter one), crafting a literary voice (chapter two), and revising historical narrative (chapter three). In particular, I examine Black laughter as an expression of Frantz Fanon's anticolonial praxis developed across his four published texts; the significance of voice in antebellum Black American literature, especially James McCune Smith's pseudonymous writings and Frank J. Webb's The Garies and Their Friends; and the redefining of Black laughter within Charles Chesnutt's The Marrow of Tradition and its revision of the 1898 Wilmington Riot; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of English.; Advisor: Christina Sharpe.; Committee: Greg Thomas, Joseph Litvak, and Sandy Alexandre.; Keywords: American literature, Black studies, and American studies.